Evaluation of Borsa İstanbul with Social Network Analysis Method - Gönçer Demiral, Dilek; Değirmenci, Nurdan (International Journal of Contemporary Economics and Administrative Sciences, 2021)
Stock markets are one of the most important markets in the financial field. Evaluating stock data in these markets is important for investors to make decisions about portfolio diversity. At this decision point, visualizing the data and presenting it in a practical and interesting way provides great convenience to investors. Social network analysis is one of the methods used effectively in the visualization of data in a short time. The purpose of this study is to reveal the relations between stocks in Borsa Istanbul 100 (BIST 100) and also to identify the stocks that have a potential role and importance in BIST 100 with social network analysis method. The centralities of degree, betweenness and pagerank of stocks were established according to their degree of correlation. According to different threshold values, stocks that are effective, strong and popular were determined in the BIST 100. And also stocks were evaluated on sectorial basis. As a result of the study, it was observed that the sequence of the stocks with different threshold values changed according to the centrality metrics. Stocks in BIST 100 are interpreted according to each centrality criterion. All findings shows, BIST 100 is not under the influence of a limited number of stocks therefore BIST 100 does not have a fragile structure.